2014
DOI: 10.9734/bjmmr/2014/6405
|View full text |Cite
|
Sign up to set email alerts
|

Dental Anxiety and Fear among Medical Field Students at Al Quds University

Abstract: Methodology: Dental anxiety scale (DAS) and Dental Fear Survey (DFS) were completed by four hundred and five students (113 males and 292 females). The population included undergraduate dental (n=198), medical (n=114) and pharmacy students (n=93). Ages ranged from 18 to 27 (the mean age of the subjects was 22.5±2.1 years). Results: Dental students were significantly less anxious (using the dental anxiety scale) compared to the other groups (medical and pharmacy students) (P<0.05). Dental students were significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 15 publications
3
7
0
Order By: Relevance
“…This was expected and is in agreement with results from other studies [16,17,21]. One obvious explanation is that the level of knowledge about dentistry, severity of dental diseases and possible inconvenience while receiving dental treatment is higher among dental students.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This was expected and is in agreement with results from other studies [16,17,21]. One obvious explanation is that the level of knowledge about dentistry, severity of dental diseases and possible inconvenience while receiving dental treatment is higher among dental students.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, conversion tables can be used to compare our findings with results of MDAS from other studies [36]. Nonetheless, levels of DA in our medical and dental students were found to be lower [16,18,21,23] or comparable [15] with that reported in studies among other medical or dental students.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Many questionnaires and scales have been established to investigate dental anxiety and fear [27,28,30,32,35,37]. The DAS is perhaps the most commonly used; it is a four-item, multiple-choice questionnaire that assesses the degree of anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that younger subjects are more likely to have dental anxiety than are elderly individuals [25,26]. Many researchers have concentrated on studying dental anxiety in university students [27][28][29][30][31][32][33][34][35][36][37], and the incidence of anxiety ranges from 11% to 27.5% among students at different universities globally [38][39][40]. Higher dental anxiety has been reported in non-dental students than in dental students, which might be because of inadequate dental health education, which leads to high dental anxiety among undergraduate students from nondental colleges [27][28][29], and additional decreases in dental anxiety have been revealed among dental students during the course of their dental training [9,41].…”
mentioning
confidence: 99%